Comparative efficacy of intravenous immunoglobulin and protein A immunoadsorption in severe anti-NMDAR encephalitis - Tang, Xuhui; Liu, Yu; Zhou, Gaoya; Tu, Ewen; Yu, Cheng; Xiong, Meishan; Lin, Cong (Frontiers in Immunology, 2025)
ObjectiveTo compare the differential effects of intravenous immunoglobulin (IVIg) and protein A immunoadsorption (PAIA) on neurological functional improvement in patients with severe anti-NMDAR encephalitis.MethodsWe retrospectively evaluated patients with severe anti-NMDAR encephalitis (modified Rankin scale, mRS ≥ 3) at the Second People’s Hospital of Hunan from January 1, 2019, to December 31, 2024. Clinical efficacy was compared between the IVIg and PAIA groups. Clinical improvement (ΔmRS ≥ 1) and favorable functional outcomes (mRS 0-2) at 30 days and 90 days were evaluated as primary outcomes. Secondary outcomes included changes in mRS and the Clinical Assessment Scale for Autoimmune Encephalitis (ΔCASE) at 30 and 90 days, length of ICU stay, and antibody titers in cerebrospinal fluid (CSF) and serum.ResultsThis study enrolled 53 patients with severe anti-NMDAR encephalitis, of whom 30 patients received IVIg and 23 patients received PAIA. The PAIA group showed a significantly higher rate of clinical improvement at 30 days after treatment compared to the IVIg group (82.61% vs. 50%, p = 0.014). However, no significant difference was found at 90 days after treatment (95.65% vs. 96.67%, p > 0.05). Furthermore, favorable functional outcomes at 30 days (17.39% vs. 6.67%) and 90 days (91.30% vs. 80.00%) showed no significant differences between the two groups (p > 0.05). Significant differences were observed in ΔmRS1 (p = 0.005), ΔmRS2 (p = 0.03), and ΔCASE1 (p = 0.027), but not in ΔCASE2 (p > 0.05). PAIA was associated with a greater reduction in antibody titers in both CSF and serum and a shorter ICU stay.ConclusionOur study demonstrates that both IVIg and PAIA are effective treatments for patients with severe anti-NMDAR encephalitis. However, PAIA demonstrates several distinct advantages, including earlier clinical improvement, faster antibody clearance, and a potential reduction in ICU stay.